Interaction energy driven biased sampling technique: a faster route to ionization spectra in condensed phase - Bose, Samik; Ghosh, Debashree (Journal of Computational Chemistry, 2017)
We introduce a computationally efficient approach for calculating spectroscopic properties, such as ionization energies (IEs) in the condensed phase. Discrete quantum mechanical/molecular mechanical (QM/MM) approaches for spectroscopic properties in a dynamic system, such as aqueous solution, need a large sample space to obtain converged estimates, especially for the cases where particle (electron) number is not conserved, such as IEs or electron affinities (EAs). We devise a biased sampling technique based on an approximate estimate of interaction energy between the solute and solvent, that accelerates the convergence and therefore, reduces the computational cost significantly. The approximate interaction energy also provides a good measure of the spectral width of the chromophores in the condensed phase. This technique has been tested and benchmarked for (i) phenol, (ii) HBDI anion (hydroxybenzylidene dimethyl imidazolinone), and (iii) thymine in water. (c) 2017 Wiley Periodicals, Inc.